The astronomy book (Big ideas simply explained, 2017)
An essential guide to milestone developments in astronomy, telling the story of our ideas about space, time, and the physics of the cosmos--from ancient times to the present day. From planets and stars to black holes and the Big Bang, take a journey through the wonders of the universe. Featuring topics from the Copernican Revolution to the mind-boggling theories of recent science, The Astronomy Book uses flowcharts, graphics, and illustrations to help clarify hard-to-grasp concepts and explain almost 100 big astronomical ideas. Covering the biographies of key astronomers through the ages such as Ptolemy, Galileo, Newton, Hubble, and Hawking, The Astronomy Book details their theories and discoveries in a user-friendly format to make the information accessible and easy to follow